Analisis Wacana Cerpen “Tinggal Matanya Berkedip-kedip” Karya Ahmad Tinjauan Aspek Sosial Budaya serta Penanda Kohesi Gramatikal dan Leksikal - Sri Widayati (Universitas Muhammadiyah Kotabumi, 2017)
Ahmad Tohari’s short story entitled “Tinggal Matanya Berkedip-kedip” seen from social aspect depicts that authority and power of a leader supported by the power of “people live in poverty”. Without civilian’s support, a leader’s power is priceless. Cohesion in grammatical aspect such as referent, substitution, ellipsis, and conjunction also appeared in the short story. The function of grammatical aspect is mainly to make the story more interesting. Cohesion in lexical aspect in the form of repetition and synonym used in the short story functions to strengthen the author’s mind which delivered.